2023
DOI: 10.3390/f14122323
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Effects of Landscape Pattern on Soundscape Perception in Residential Green Spaces

Jiang Liu,
Yi-Jun Huang,
Zhu Chen
et al.

Abstract: Soundscape quality in green spaces of residential areas directly contributes to residents’ quality of life. It has close relationships with landscape characteristics, which should be considered in landscape planning and design processes in residential areas. Accordingly, this study proposed a new perspective on the interrelationships between soundscape perception and landscape pattern on multi-scale, based on a case study of 30 residential green spaces in Fuzhou, China. Percentage of Landscape (PLAND), Patch D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Moreover, our research collections extend to the development of predictive models for soundscape perception, which are founded upon the acquisition of sufficient data. Liu et al explored a new perspective on the interrelationships between soundscape perception and landscape pattern on a multi-scale [8]. The authors confirmed that the scale effect of landscape patterns can affect soundscape perception based on 30 residential green spaces.…”
Section: Summary Of Articles Included In the Special Issuementioning
confidence: 97%
“…Moreover, our research collections extend to the development of predictive models for soundscape perception, which are founded upon the acquisition of sufficient data. Liu et al explored a new perspective on the interrelationships between soundscape perception and landscape pattern on a multi-scale [8]. The authors confirmed that the scale effect of landscape patterns can affect soundscape perception based on 30 residential green spaces.…”
Section: Summary Of Articles Included In the Special Issuementioning
confidence: 97%